An analytic report of studies on Sadeq Hedayat's works from1330to1381 - Ebrahim Noorbakhsh; Saeed Hessampour (تاریخ ادبیات)
Sadeq Hedayat is the most influential contemporary author. Different books and articles have been written about his character and works. This essay intends to study aspects of Hedayat-studies based on current research about him. It then analyses the process of Hedayat-studies from 1330 to1380 in periods of 10 years. Results indicate that in the 1330s during which Hedayat’s researchers experienced how to study Hedayat, 51 articles and 12books have been written about his mental features, his inspiration from other non-Persian authors, and his inclination to secret sciences. In the 1340s, 124 articles and six books were published about Hedayat and especially about his stories. In this decade, new aspects of his life and works have been considered by Hedayat-researchers. In the 1350s, 145 articles and eight books were printed about his suicide and other general topics. In the1360s, experience of researchers about Hedayat-studies increased and authors relying on their information about literary criticism, they analyzed Hedayat-studies. In this time, 160 articles and four books were published about him. In the1370s, it was wonderfully observed that the rate of topics and issues about Hedayat developed. In this period, 170 articles and 45 books were written about him. It can be concluded that Hedayat-studies have been improving whether in the point of quantity or quality from 1330 to 1381.